A biological tool to combat against multidrug-resistant Salmonella isolated from poultry of Chittagong City, Bangladesh - Mahbuba, A; Islam, S; Mazumdar, RM; Fakruddin, M; Das, S; Bhuiyan, H; Prodhan, SH (International Journal of Natural Sciences, 2012)
Thirty two strains of Salmonella were isolated from the samples collected from different poultry farm of Chittagong City. Isolated organisms were then subjected to antibiotic sensitivity test against seven different standard antibiotics. Most of the strains tested were resistant to four antibiotics; 93.75% were resistant to co-trimaxazole, while 90.62% were resistant to cephotaxime, nalidixic acid and Tetracycline each. In this study, ciprofloxacin and gentamicin were found to be the most potent drugs, (78.125%) were sensitive to Ciprofloxacin & (78.125%) were sensitive to gentamicin. Antimicrobial activity of bark extract of T. arjuna against 13 selected isolates of Salmonella were then determined. During the course of the anti-microbial screening it was found that among the 13 selected isolates, Salmonella (L3-B1), Salmonella (L5-X4), Salmonella (F-X2) and Salmonella (S2-B1) showed good sensitivity to crude extract of T. arjuna. International Journal of Natural Sciences (2012), 2(3):71-75 DOI: http://dx.doi.org/10.3329/ijns.v2i3.12135